2022
DOI: 10.3389/fped.2022.859092
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound Characteristics in Neonates With Positive Real Time Polymerase Chain Reaction for SARS-CoV-2 on a Tertiary Level Referral Hospital in Mexico City

Abstract: IntroductionAcute respiratory syndrome secondary to SARS-CoV-2 virus infection has been declared a pandemic since December 2019. On neonates, severe presentations are infrequent but possible. Lung ultrasound (LUS) has been shown to be useful in diagnosing lung involvement and following up patients, giving more information, and reducing exposure compared to traditional examination.MethodsLUS was performed after the diagnosis of SARS-CoV-2 infection with respiratory Real Time Polymerase Chain Reaction RT-PCR wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 31 publications
2
18
1
Order By: Relevance
“…Most of the frequent transmission types were postnatal ones, according to the idea that vertical transmission was at low risk [ 5 ]. Moreover, the rate of postnatal transmission reported by Ibarra-Ríos et al was 91%, pretty much similar to the 84.21% found in our report [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Most of the frequent transmission types were postnatal ones, according to the idea that vertical transmission was at low risk [ 5 ]. Moreover, the rate of postnatal transmission reported by Ibarra-Ríos et al was 91%, pretty much similar to the 84.21% found in our report [ 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study’s mean of LUSS was 12.21 ± 3.56 (S.D) which is higher than Li et al’s study (8.40 ± 1.70) and was included in the range of Ibarra-Ríos et al study (11.2–16) which is scored using a 10-area score [ 18 , 25 ]. The most common signs found in the newborns included in study were represented by B-lines changes, a fact confirmed also by Musolino et al [ 24 , 29 ].…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations